ANALISIS FLYPAPER EFFECT PADA BELANJA DAERAH PEMERINTAH PROVINSI DI INDONESIA TAHUN ANGGARAN 2016 - Nurhayati Nurhayati; Arif Wicaksono (Media Ekonomi, 2017)
This study aims to analyze whether there is a Flypaper Effect in the Implementation of Regional Expenditur es for the realization of the 2016 APBD and also estimate the effect of PAD and DAU on Regional Expenditures. The method of analysis uses analysis of Multiple Linear Regression using a sample of 34 provinces in Indonesia. The results of the study indicate that there is a positive influence between PAD and DAU on Regional Expenditures. In addition, the results of the study revealed the results that there was a Flypaper Effect in the Implementation of Regional Expenditures in the Realization of Provincial Government Budget in the Year 2016. The flypaper effect that occurred in the 2016 Fiscal Year in Indonerisa showed that the provincial government in Indonesia had not been able to create fiscal independence. from the still coherent transfer fund coefficient compared to the PAD coefficient.